2017
DOI: 10.1016/j.ypmed.2017.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity trajectories during midlife and subsequent risk of physical functioning decline in late mid-life: The Study of Women's Health Across the Nation (SWAN)

Abstract: The purpose of this study was to examine the importance of midlife physical activity on physical functioning in later life. Data are from 1771 Study of Women’s Health Across the Nation (SWAN) participants, aged 42–52 (46.4 ± 2.7) years at baseline (1996–97). Latent class growth analysis was used to identify physical activity trajectory groups using reported sports and exercise index data collected at seven time-points from baseline to Visit 13 (2011–13); objective measures of physical functioning performance w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
37
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 33 publications
7
37
1
Order By: Relevance
“…While several studies showed that health-related factors like smoking or high BMI were associated with poor PA outcomes [ 21 , 47 , 48 , 49 , 50 ], the results of our study were not that concise. In our study, only overweight and obesity compared to normal weight subjects had decreased odds for being in the stable active trajectory, whereas smoking or having a cardiovascular risk factor were not associated with the PA trajectory.…”
Section: Discussioncontrasting
confidence: 96%
See 2 more Smart Citations
“…While several studies showed that health-related factors like smoking or high BMI were associated with poor PA outcomes [ 21 , 47 , 48 , 49 , 50 ], the results of our study were not that concise. In our study, only overweight and obesity compared to normal weight subjects had decreased odds for being in the stable active trajectory, whereas smoking or having a cardiovascular risk factor were not associated with the PA trajectory.…”
Section: Discussioncontrasting
confidence: 96%
“…Subsequent multivariable regression analyses revealed that being in the stable active trajectory was predicted by only one of the included socio-demographic factors, namely high education (more than 12 years compared to less than 10 years). This is partially in line with several other studies showing that male sex, lower age, high education, and/or a high household income were predictors for favorable PA trajectories (increasing or persistently active) [ 17 , 21 , 33 , 42 , 43 , 44 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Instead, the GBTM trajectories suggest that prior PA dictates PA in old age. This is consistent with some other GBTM studies using continuous measures of PA that have also identified trajectories that do not typically overlap during this life period 25 37 38. In contrast, a recent study among retired adults using retrospectively reported PA showed that trajectories are more changeable across the life course than suggested by the present findings 26.…”
Section: Discussionsupporting
confidence: 92%
“…Recent research suggests their sedentary time is also increasing, compounding their risk [5] -daily leisure-time sitting of over 6 versus less than 3 h has been linked to ∼40% higher all-cause death rate, independent of PA [6]. To increase the odds of healthy ageing in this population, research is urgently needed to expand the limited evidence base on key factors to target in developing effective interventions which simultaneously target increased activity and reduced sitting across the menopausal transition [7].…”
Section: Introductionmentioning
confidence: 99%